Pemberdayaan Remaja Masjid melalui Literasi Hukum Perkawinan Berbasis Maqashid Syariah untuk Mencegah Perkawinan Anak - Miti Yarmunida; Iim Fahimah; Muhammad Arkanul Iman; Muhammad Irvan Syahril; Yunia Putri (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service activity aims to empower mosque youth through maqashid-based Islamic family law literacy as a preventive strategy against child marriage. The persistence of child marriage remains a significant social issue, particularly in coastal and rural communities, and is influenced by limited legal awareness, entrenched socio-cultural norms, and partial religious understanding that tends to emphasize formal legality rather than substantive objectives. This program applies a Community-Based Research (CBR) approach involving 47 mosque youth as active participants. The implementation includes several stages, namely social mapping to identify community conditions, development of legal literacy modules based on maqashid al-shariah, participatory training sessions, and the formation of peer educators to ensure program sustainability. Data were collected through observation, interviews, focus group discussions, and pre- and post-tests to measure changes in participants’ knowledge and attitudes. The results indicate a significant increase in legal literacy, with an improvement of 45–60%, along with a notable shift in participants’ perspectives toward delaying marriage until achieving adequate psychological, social, and economic readiness. The maqashid-based approach proved effective in transforming normative religious perspectives into more contextual and substantive legal awareness. This activity highlights the strategic role of mosque-based empowerment as a culturally relevant and sustainable approach to strengthening community legal awareness and preventing child marriage, particularly by positioning youth as agents of social change within their communities.